Distribution patterns of Acidobacteriota in different fynbos soils. - Tersia Andrea Conradie; Karin Jacobs (PLoS ONE)
The Acidobacteriota is ubiquitous and is considered as one of the major bacterial phyla in soils. The current taxonomic classifications of this phylum are divided into 15 class-level subdivisions (SDs), with only 5 of these SDs containing cultured and fully described species. Within the fynbos biome, the Acidobacteriota has been reported as one of the dominant bacterial phyla, with relative abundances ranging between 4-26%. However, none of these studies reported on the specific distribution and diversity of the Acidobacteriota within these soils. Therefore, in this study we aimed to first determine the relative abundance and diversity of the Acidobacteriota in three pristine fynbos nature reserve soils, and secondly, whether differences in the acidobacterial composition can be attributed to environmental factors, such as soil abiotic properties. A total of 27 soil samples were collected at three nature reserves, namely Jonkershoek, Hottentots Holland, and Kogelberg. The variable V4-V5 region of the 16S rRNA gene was sequenced using the Ion Torrent S5 platform. The mean relative abundance of the Acidobacteriota were 9.02% for Jonkershoek, 14.91% for Kogelberg, and most significantly (p<0.05), 18.42% for Hottentots Holland. A total of 33 acidobacterial operational taxonomic units (OTUs) were identified. The dominant subdivisions identified in all samples included SDs 1, 2, and 3. Significant differences were observed in the distribution and composition of these OTUs between nature reserves. The SD1 were negatively correlated to soil pH, hydrogen (H+), potassium (K+) and carbon (C). In contrast, SD2, was positively correlated to soil pH, phosphorus (P), and K+, and unclassified members of SD3 was positively correlated to H+, K, and C. This study is the first to report on the specific acidobacterial distribution in pristine fynbos soils in South Africa.